2016
DOI: 10.2459/jcm.0000000000000151
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity is not impaired after acute alcohol ingestion

Abstract: The usage of alcohol is widespread, but the effects of acute alcohol ingestion on exercise performance and the stress hormone axis are not fully elucidated.We studied 10 healthy white men, nonhabitual drinkers, by Doppler echocardiography at rest, spirometry, and maximal cardiopulmonary exercise test (CPET) in two visits (2-4 days in between), one after administration of 1.5 g/kg ethanol (whisky) diluted at 15% in water, and the other after administration of an equivalent volume of water. Plasma levels of NT-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…This finding is in line with randomised trials indicating that acute excessive drinking does not affect peak VO 2 . 45,46 Previous research suggested that heavy episodic drinking counteracts the putative protective effect of low-to-moderate moderate consumption. 6 However, the association between average alcohol consumption and peak VO 2 persisted after adjustment for heavy episodic drinking, and the association was not modified by heavy episodic drinking.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with randomised trials indicating that acute excessive drinking does not affect peak VO 2 . 45,46 Previous research suggested that heavy episodic drinking counteracts the putative protective effect of low-to-moderate moderate consumption. 6 However, the association between average alcohol consumption and peak VO 2 persisted after adjustment for heavy episodic drinking, and the association was not modified by heavy episodic drinking.…”
Section: Discussionmentioning
confidence: 99%
“…* apresentou efeito significante em função do tempo (P= 0,000). , 1993;MCNAUGHTON;PREECE, 1986;SUTER;SCHUTZ, 2008;WANG et al, 1995 1984a;FERREIRA et al, 2004;POPOVIC et al, 2016) 2005). De fato, do ponto de vista fisiológico, a ingestão de cerveja promove maior consumo de oxigênio devido a alterações no metabolismo energético e no sistema cardiovascular (FERREIRA et al, 2004;WANG et al, 1995).…”
Section: Efeitos Daunclassified